Learning Shell Scripting with Zsh - Festari, Gaston (Packt Publishing, Limited, 2014)
A step-by-step tutorial that will teach you, through real-world examples, how to configure and use Zsh and its various features. If you are a system administrator, developer, or computer professional involved with UNIX who are looking to improve on their daily tasks involving the UNIX shell, "Learning Shell Scripting with Zsh" will be great for you. It's assumed that you have some familiarity with an UNIX command-line interface and feel comfortable with editors such as Emacs or vi.